0046 Handover in recovery; a high fidelity in-situ simulation training package to improve the quality of theatre recovery handover and patient safety. (2nd November 2015) - Penney, Lisa; Fogg, David; Russell, Scott; Boss, Laurence; Isherwood, Peter
Abstract : Background/context: Handover has been identified as a crucial element of communication in healthcare and other industries. 1 High fidelity simulation training has been demonstrated to change team behaviour. 2 We have developed and are implementing a high fidelity in-situ training package to improve recovery handover, communication and hence patient safety. Methodology: A survey of theatre recovery staff and critical incident reviews has highlighted sub-optimal handover as being a barrier to patient safety in recovery in our institution. Using the data from these sources we identified four learning objectives: Receiving a handover Giving a handover Initial patient assessment to incorporate into handover Escalation to available sources of support. Working with these and in collaboration with colleagues running a project at GSTT 3 we have created this course centred on scenarios with learning objectives to match the above. Our learners are the recovery nursing staff with a plan to roll out to ODPs and anaesthetists in the future. The sessions are carried out in a formative manner, the learners have an introduction to the simulated environment and the wireless manikin, they encounter three scenarios per session with a subsequent debrief to identify learning outcomes. Results/outcomes: Pre and post course TeamSTEPPS Teamwork Perceptions Questionnaire completed by all recovery staff. Learner feedback from all sessions run prior to ASPiH in November (20 sessions). Potential impact: To improve handover and communication in recovery, precipitating a cultural change in the expectations of handover and communication in theatres recovery. Improving patient safety and quality of care in recovery. References: Jeffcott SA, Evans SM, Cameron PA, Chin GSM, Ibrahim JE. Improving measurement in clinical handover. Qual Saf Health Care 2009;18:272–277 Schmutz J, Manser T. Do team processes really have an effect on clinical performance? A systematic literature review. Br J Anaesth 2013;110(4):529–44 In-Situ Recovery Simulation Training at GSTT, Ongoing